Democratic citizenship in flux - Bayer, Markus 1983-; Schwarz, Oliver 1976-; Stark, Toralf 1981- (Edition Politik, 2020)
Long description: Traditionally, citizenship has been defined as the legal and political link between individuals and their democratic political community. However, traditional conceptions of democratic citizenship are currently challenged by various developments like migration, the rise of populism, increasing polarization, social fragmentation, and the challenging of representative democracy as well as developments in digital communication technology. Against this background, this book reflects recent conceptions of citizenship by bringing together insights from different disciplines, such as political science, sociology, economics, law, and history